IDSov and the silent data revolution: Indigenous Peoples and the decentralized building blocks of web3 - Dobson, Dillon; Fernandez, Adam (Frontiers in Research Metrics and Analytics, 2023)
This article explores the technology underpinning the decentralized data revolution and encourages Indigenous Peoples (IPs) to secure their Indigenous Data Sovereignty (IDSov) over the Metaverse and Web3. More specifically, this article will survey blockchain technologies, exploring some disturbing colonial uses and providing an international legal framework that IPs can use to advance their IDSov internationally and domestically. This article will consider the role that cryptocurrencies, smart contracts, decentralized oracles, non-fungible tokens (NFTs), decentralized finance (DeFi), and decentralized autonomous organizations (DAOs) might play in advancing IDSov as it relates to western conceptualizations of Web3 and the Metaverse. The worldwide web's global data structure is undergoing a seismic shift that will significantly impact IPs. As inherent sovereigns, IPs are uniquely positioned to use and regulate these technologies in manners consistent with their cultural values and international indigenous human rights instruments. However, the march toward Web3 also looms menacingly over IPs. As such, we intend to examine IPs' novel risks and opportunities with Web3 and the Metaverse. We conclude by encouraging IPs to become fluent in the minutia of these technologies and to exert their inherent sovereignty over these nascent technologies in international and domestic arenas by building culturally informed systems to address their particularized needs. Future research should look toward the specific hurdles, and successes IPs are experiencing as they apply the technologies and principles discussed here.